First observation of a Baryonic B0s decay - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2017)
We report the first observation of a baryonic B0s decay, B0s→p¯ΛK−, using proton-proton collision data recorded by the LHCb experiment at center-of-mass energies of 7 and 8 TeV, corresponding to an integrated luminosity of 3.0 fb−1. The branching fraction is measured to be B(B0s→p¯ΛK−)+B(B0s→¯pΛK+)=[5.46±0.61±0.57±0.50(B)±0.32(fs/fd)]×10−6, where the first uncertainty is statistical and the second systematic, the third uncertainty accounts for the experimental uncertainty on the branching fraction of the B0→p¯Λπ− decay used for normalization, and the fourth uncertainty relates to the knowledge of the ratio of b-quark hadronization probabilities fs/fd.